European integration, 1950-2003 : superstate or new market economy? - Gillingham, John, 1943- (Cambridge University Press, 2003)
Integration is the most significant European historical development in the past fifty years, eclipsing in importance even the collapse of the USSR. Yet, until now, no satisfactory explanation is to be found in any single book as to why integration is significant, and where it is headed.